Culture, Society, Daily Life and Politics During Stalinism: A Historiographical Essay - Lida, Miranda (Revista de Historia Social y de las Mentalidades, 2024)
Last years, there were great progresses on the studies about the sovietic era. We introduce on this article a historiographical approach on several studies developed on the last decades -since the collapse of Soviet Union- at the anglo-saxon historiography focused pn the study of value systems, cultural and social practices at the time of the Stalin regime. The sovietic society had to deal with deep economic transformations as the results of the first five-year plans, the political purges and the utopia of a new sovietic man. Stalinism supposed a great transformation for a country that still remained mostly rural on 1917. The depth of this revolutionary change can be observed not only on government and economy, but also on ordinary life, society, culture, values and costumes. These are the axes that more contributed to illuminate the new discussions on this issue.
Keywords: Stalinism; Historiography; Daily Life; Cultural Practices